Transcriptome Analysis of Stephania yunnanensis and Functional Validation of CYP80s Involved in Benzylisoquinoline Alkaloid Biosynthesis - Wenlong Shi; Qishuang Li; Xinyi Li; Linglong Luo; Jingyi Gan; Ying Ma; Jian Wang; Tong Chen; Yifeng Zhang; Ping Su; Xiaohui Ma; Juan Guo; et al. (Molecules)
The medicinal plant Stephania yunnanensis is rich in aporphine alkaloids, a type of benzylisoquinoline alkaloid (BIA), with aporphine being the representative and most abundant compound, but our understanding of the biosynthesis of BIAs in this plant has been relatively limited. Previous research reported the genome of S. yunnanensis and preliminarily identified the norcoclaurine synthase (NCS), which is involved in the early stages of the BIA biosynthetic pathways. However, the key genes promoting the formation of the aporphine skeleton have not yet been reported. In this study, based on the differences in the content of crebanine and several other BIAs in different tissues, we conducted transcriptome sequencing of roots, stems, and leaves. We then identified candidate genes through functional annotation and sequence alignment and further analyzed them in combination with the genome. Based on this analysis, we identified three CYP80 enzymes (SyCYP80Q5-1, SyCYP80Q5-3, and SyCYP80G6), which exhibited different activities toward (S)- and (R)-configured substrates in S. yunnanensis and demonstrated strict stereoselectivity enroute to aporphine. This study provides metabolomic and transcriptomic information on the biosynthesis of BIAs in S. yunnanensis, offers valuable insights into the elucidation of BIA biosynthesis, and lays the foundation for the complete analysis of pathways for more aporphine alkaloids.